THE EFFECT OF POP UP BOOK IN READING COMPREHENSION - Arisandi, Risa; Rafi, Muhammad Farhan (Prosiding Conference on Research and Community Services, 2019)
This research was conducted to investigate the effect of pop up book applied in teaching reading comprehension of narrative text. The design of this research was quasi experimental research because the researcher cannot choose the subject randomly. The subject of this research was the eight grade students of SMPN 2 Bareng. The subject of this reseach consisted of class VIII A with 25 students as the experimental group and class VIII B with 23 students as the control group. The researcher had used test as the instrument for collecting the data. The researcher had three steps in this research. That were giving pre test for both two groups, doing treatment, and giving post test. Based on the Analysis of Covarience (ANCOVA), the result of this research had shown that Sig. of bacground knowledge of students on reading comprehension is 0,000 and the Sig. of media of pop up book is 0,000 as well. It was lower than 0,05. It means that the H0 is rejected. It declared that there is asignificant difference with students achievement who are taught in reading comprehension of narrative text by using pop up book than students who are taught without using pop up book. This result was also supported by the Partial Eta Square table which had shown that the value of the media of pop up book was 0,388 and 0, 343 for the value of the bacground knowledge of students on reading comprehension. The value of the pop up book as media was higher than the value of the bacground knowledge of students on reading comprehension. It means that the result of this research is surely influenced by the treatment manipulated by the researcher and it was not affected by the students bacground knowledge of students on reading comprehension.